Biomechanical determinant of sitting comfort in cycling, a case study series - Scholler, V.; Pirlot, T.; Groslambert, A.; Grappe, F. (Journal of Science and Cycling, 2021)
Cycling can lead to traumatic injuries which are caused by a bad interaction between the cyclist's buttocks and the saddle, causing an alteration of the perception of the sitting comfort (Breda et al., 2005; Larsen et al., 2018). Shear forces on buttock tissues seemed to be associated with the seating perceived comfort during driving. Yet, no studies investigated similar results during cycling. Therefore, 4 males and 1 female competitive cycling performed a 20 min cycling exercise on a treadmill, before and after a bikefitting procedure aiming to improve their initial low sitting comfort. This exercise was composed of 4 blocks of 5 minutes at 1, 3, 6, and 9% slopes. At the end of each block, tangential forces in the anterior-posterior and medial-lateral direction transmitted to the seat tube were measured with a custom-made sensor. After the fitting optimization session, there was a statistical increase in the mean tangential force amplitude in the anterior-posterior direction (+29 ± 29%, p<0.05, d>0.8) and in the medial-lateral force (+31 ± 26%, p<0.05, d>0.8) at 1% slope, but not at 3, 6 and 9% slopes. Moreover, the perceived sitting comfort increased after the fitting session (p<0.001, +180 ± 109 %). The increase in tangential forces transmitted from the cyclists to the seat tube in the anterior-posterior and medial-lateral direction at a slope of 1% could be caused by the better stability of the pelvic on the saddle after the fitting session. It suggested a reduction in the dissipation of the tangential forces generated by the cyclists into shear forces between buttock tissues and the saddle, which could improve the perceived sitting comfort. Controlling such biomechanics variable would allow preventing some saddle related injuries.